ANTIMICROBIAL ACTIVITY OF RIND EXTRACTS OF PUNICA GRANATUM LINN. - J. SANGEETHA; K. VIJAYALAKSHMI (The Bioscan, 2011)
The present investigations evaluates the antimicrobial activity of crude extracts from the rinds of Punica granatum against selected gram positive, gram negative bacteria and fungal strains. In this study, we investigated the in vitro antimicrobial activity of rinds of ganesh and Kabul variety in different solvent like ethyl acetate, ethanol, methanol, water and acetone are used against the different strains. The zone of inhibition obtained was dose dependent and methanol extract of ganesh variety was found to be the most effective antibacterial agent as compared to the aqueous extract of the same variety. In case of Kabul variety the ethyl acetate extract was effective against Bacillus, E.coli, Pseudomonas, Staphylococcus and Candida. The Aqueous extract was also effective against Aeromonas, Bacillus, E.coli, Pseudomonas, Staphylococcus, Vibrio and Candida. The methanolic rind extract of Punica granatum ganesh variety showed high antimicrobial activity against each of the tested strains, and these values ranged from 31.75 to 1000 μg/mL and in case of Kabul variety the ethyl acetate rind extract showed activity from 62.5 to 500 μg/mL. It can be concluded that methanolic rind extract of ganesh variety has the potential to provide an effective treatment for infectious disease caused by various microorganisms.